‘And I built this Everlasting Peak for him’. The Two Scribal Traditions of the Hittites and the NA4ḫekur SAG.UŠ - Balza, Maria Elena (Altorientalische Forschungen, 2011)
During the Late Hittite Empire, in the second half of the 13 th century BC, there is a change in the way history is written, as the Anatolian hieroglyphic script seems to become the privileged medium for communicating royal ideology. Hieroglyphic was considered the most appropriate means for the diffusion of the most important messages, i.e. who the true king was and who his protective god was. The present paper deals with the contemporary use of two writing systems by the last Hittite kings and with the association between hieroglyphic inscriptions and the monuments called NA4 ḫekur SAG.UŠ documented in a few Hittite texts. Additionally, it discusses some hypotheses on the location of the NA4 ḫekur SAG.UŠ mentioned in the preserved cuneiform sources.